2021
DOI: 10.3389/fmicb.2021.749218
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Weissella confusa LM1 and Comparative Genomic Analysis

Abstract: The genus Weissella is attracting an increasing amount of attention because of its multiple functions and probiotic potential. In particular, the species Weissella confusa is known to have great potential in industrial applications and exhibits numerous biological functions. However, the knowledge on this bacterium in insects is not investigated. Here, we isolated and identified W. confusa as the dominant lactic acid bacteria in the gut of the migratory locust. We named this strain W. confusa LM1, which is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…W. cibaria (101), W. confusa (88), and W. jogaejeotgali (83) are the three species that encode most CAZyme genes in their genomes. Our identification results are consistent with those of a previous study ( Yuan et al, 2021 ), which found that W. confusa and W. cibaria metabolize carbohydrates and could be beneficial in several applications. These findings could also imply that most Weissella species, and especially W. cibaria and W. confusa , specialize in carbohydrate metabolism, which helps control mass degradation in the fermentation process.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…W. cibaria (101), W. confusa (88), and W. jogaejeotgali (83) are the three species that encode most CAZyme genes in their genomes. Our identification results are consistent with those of a previous study ( Yuan et al, 2021 ), which found that W. confusa and W. cibaria metabolize carbohydrates and could be beneficial in several applications. These findings could also imply that most Weissella species, and especially W. cibaria and W. confusa , specialize in carbohydrate metabolism, which helps control mass degradation in the fermentation process.…”
Section: Resultssupporting
confidence: 92%
“…However, W. cibaria was not the only species whose pan-genome showed a tendency to be closed. In a previous report ( Yuan et al, 2021 ), the pan-genome of 39 W. confusa strains was also open but in this study, when we analyzed 77 strains of W. confusa , the pan-genome status tended to be closed. In addition, we observed that the core genome sizes of W. cibaria strains seemed to be stable after sequencing around 50 genomes including ≈ 1,200 genes ( Supplementary Figure 5B ).…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Indeed, some very recent research has looked into the probiotic potential of LAB obtained from insect guts [64,75,76]. A complete genome sequence of Weissella confusa LM1, found in the gut of the migratory locust, indicated the ability to adapt to different ecological niches [77]. While there are studies on microbiological communities (including LAB) in grasshoppers (Locusta migratoria migratorioides) sold for human consumption [78], to our knowledge, this is the first report studying the probiotic potentialities of locust-derived LAB.…”
Section: Discussionmentioning
confidence: 99%
“…Culture-independent approaches including PCR-DGGE and next-generation sequencing approaches such as metagenetics and metagenomics have allowed the detection of weissellas in various ecological niches ( Table 2 ). Whole-genome sequencing is another approach that is being widely used to identify and characterize weissellas (Benomar et al, 2011 ; Kim et al, 2011 ; Amari et al, 2012 ; Lee J. H. et al, 2012 ; Figueiredo et al, 2014a , b , 2015 ; Tanizawa et al, 2014 ; Malik et al, 2016 ; Heng et al, 2017 ; Ku et al, 2017 ; Li et al, 2017 ; Du et al, 2018 ; Garcia-Cancino et al, 2019 ; Kwak et al, 2019 ; Panthee et al, 2019 ; Lin et al, 2020 ; Månberger et al, 2020 ; Baugh et al, 2021 ; Contente et al, 2021 ; Jang et al, 2021 ; Patrone et al, 2021 ; Yuan et al, 2021 ; Apostolakos et al, 2022 ; Fanelli et al, 2022 ; Fukuda and Nolasco-Hipolito, 2022 ; Surachat et al, 2022 ; Teixeira et al, 2022 ).…”
Section: Detection and Typing Of Weissellamentioning
confidence: 99%